Fine particulate matter exposure during pregnancy and infancy and incident asthma - Jung, Chau-Ren; Chen, Wei-Ting; Tang, Yu-Hsin; Hwang, Bing-Fang (Journal of allergy and clinical immunology, 2019)
Lung development is a multistage process from conception to the postnatal period, disruption of which by air pollutants can trigger later respiratory morbidity. We sought to evaluate the effects of weekly average fine particulate matter (particulate matter with an aerodynamic diameter less than 2.5 μm [PM2.5]) exposure during pregnancy and infancy on asthma and identify vulnerable times to help elucidate possible mechanisms of the effects of PM2.5 on asthma symptoms. A birth cohort study including 184,604 children born during 2004-2011 in Taichung City was retrieved from the Taiwan Maternal and Child Health Database and followed until 2014. A daily satellite-based hybrid model was applied to estimate PM2.5 exposure for each subject. A Cox proportional hazard model combined with a distributed lag nonlinear model was used to evaluate the associations of asthma with PM2.5 exposure during pregnancy and infancy. The birth cohort contained 34,336 asthmatic patients, and the mean age of children given a diagnosis of asthma was 3.39 ± 1.78 years. Increased exposure to PM2.5 during gestational weeks 6 to 22 and 9 to 46 weeks after birth were significantly associated with an increased incidence of asthma. The exposure-response relationship indicated that the hazard ratio (HR) of asthma increased steeply at PM2.5 exposure of greater than 93 μg/m3 during pregnancy. Additionally, the HRs remained significant with postnatal exposure to PM2.5 between 26 and 72 μg/m3 (range, 1.01-1.07 μg/m3), followed by a sharp increase in HRs at PM2.5 exposure of greater than 73 μg/m3. Both prenatal and postnatal exposures to PM2.5 were associated with later development of asthma. The vulnerable time windows might be within early gestation and midgestation and infancy. [Display omitted]